2007
DOI: 10.1016/j.cellbi.2007.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the monovalent ion fluxes in U937 cells under the balanced ion distribution: Recognition of ion transporters responsible for changes in cell ion and water balance during apoptosis

Abstract: Unidirectional (22)Na, Li(+) and Rb(+) fluxes and net fluxes of Na(+) and K(+) were measured in U937 human leukemic cells before and after induction of apoptosis by staurosporine (1 microM, 4 h) to answer the question which ion transporter(s) are responsible for changes in cell ion and water balance at apoptosis. The original version of the mathematical model of cell ion and water balance was used for analysis of the unidirectional ion fluxes under the balanced distribution of major monovalent ions across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 22 publications
2
26
1
1
Order By: Relevance
“…This inverse problem is much harder than finding concentrations from known parameters, and we approach it by trial and error. In the case of U937 cells, [Na] i , [K] i , [Cl] i , cell water content per unit of A , the pump coefficient β and OSOR were measured as described previously [11,12,13,14,15]. These data proved sufficient to find a unique set of parameters corresponding to the balanced state for a model that includes the pump, Na + , K + , Cl - channels and a single type of cotransport.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This inverse problem is much harder than finding concentrations from known parameters, and we approach it by trial and error. In the case of U937 cells, [Na] i , [K] i , [Cl] i , cell water content per unit of A , the pump coefficient β and OSOR were measured as described previously [11,12,13,14,15]. These data proved sufficient to find a unique set of parameters corresponding to the balanced state for a model that includes the pump, Na + , K + , Cl - channels and a single type of cotransport.…”
Section: Resultsmentioning
confidence: 99%
“…Salts were of analytical grade and were from Reachem (Russia). The experimental methods used in this work have been described in detail earlier [11,12,13,14,15]. Briefly, intracellular K + , Na + and Rb + content was analyzed by flame emission spectrometry, Cl - content was measured using 36 Cl - isotope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…-вовлечен в регуляцию разнооб разных клеточных функций (через влияние на кле точный объем), включая пролиферацию, рост, программируемую гибель и некроз [11][12][13][14].…”
Section: оригинальные исследованияunclassified
“…It was reported that at least 14 species of K + channels are involved somehow in apoptosis of various cells [2]. However, calculation of the changes in ion and water balance caused by an increase in the integral permeability of K + channels showed that significant cell shrinkage in apoptosis due to increase in the permeability of the K + channels can occur only under specific conditions [14][15][16]. In addition, an increase in the integral permeability 188 of K + channels conventionally associated with the opening of channels should lead to hyperpolarization of apoptotic cells whereas depolarization was mostly observed [12,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%